A taxonomic survey of pteridophytic flora of Lalmai Pahar and Mainamati of Cumilla district, Bangladesh (Dhaka University Journal of Biological Sciences, 2024)
This study aims to investigate the pteridophytic flora of the Lalmai Pahar, Mainamati, located at the Cumilla district of Bangladesh. Despite the absence of extensive pteridophyte surveys in this hilly forest, it is known to harbour a diverse range of pteridophyte species. This study presents a survey of the pteridophyte diversity within the specified area, documenting a total of 27 taxa. The voucher specimens have been deposited at the Salar Khan Herbarium, Department of Botany at the University of Dhaka.Dhaka Univ. J. Biol. Sci. 33(1): 1-21, 2024 (January)